Demonstration of an optically stimulated luminescence (OSL) material with reduced quenching for proton therapy dosimetry: MgB4O7:Ce, Li. (March 2022) - Yukihara, E.G.; Christensen, J.B.; Togno, Michele
Abstract: The objective of this work is to demonstrate that MgB4 O7 :Ce, Li, a new optically stimulated luminescence (OSL) dosimetric material, shows improved response for proton therapy dosimetry, with less reduction in luminescence detector efficiency with the particle linear energy transfer (LET). MgB4 O7 :Ce, Li was synthesized and its luminescence efficiency as a function of LET was characterized for dose-averaged LET values from 0.73 keV/μm up to 74.9 keV/μm using proton, 4 He, and 12 C ion beams. Commercial Al2 O3 :C OSLDs were also used for comparison. Monte Carlo simulations were used to predict the material's response in pristine and spread-out Bragg peaks (SOBP), suggesting the MgB4 O7 :Ce, Li would offer minimum quenching in proton beams of energies relevant to radiotherapy. This prediction was confirmed by irradiations of MgB4 O7 :Ce, Li and Al2 O3 :C along SOBPs from proton beams. The results demonstrate that new OSL materials optimized for proton dosimetry can be developed using their dose response to low-LET radiation as a guide during material development. HIGHLIGHTS: A new OSL material, MgB4 O7 :Ce, Li, was investigated for proton therapy dosimetry. Monte Carlo simulations were used to predict the material's response for proton and carbon ion beams. Simulations indicate that MgB4 O7 :Ce, Li should perform well for proton beams. Predictions were confirmed experimentally using clinically relevant proton beams.